2018
DOI: 10.1111/epi.14445
|View full text |Cite
|
Sign up to set email alerts
|

Quality of antiepileptic drugs in sub‐Saharan Africa: A study in Gabon, Kenya, and Madagascar

Abstract: No counterfeiting was observed. However, inadequate AED storage conditions are likely to lead to ineffective and possibly dangerous AEDs, even when good-quality AEDs are initially imported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
2
10
2
Order By: Relevance
“…Our result on affordability was similar to a previous multicenter study conducted in 46 countries which reported the day wage patient price of generic carbamazepine was less than 5.0 day in all healthcare facilities, although this study pulled data from developing and developed countries 7 . The proportion of poor‐quality AEDs found in our study (15.0%) was lower than that observed in a study performed in sub‐Saharan Africa 8 which reported 32.3% of poor quality. In that study, carbamazepine and sodium valproate were the poorest in terms of quality, probably due to high sensitivity to humidity and heat under tropical conditions, whereas our study found poor quality only for phenobarbital samples.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our result on affordability was similar to a previous multicenter study conducted in 46 countries which reported the day wage patient price of generic carbamazepine was less than 5.0 day in all healthcare facilities, although this study pulled data from developing and developed countries 7 . The proportion of poor‐quality AEDs found in our study (15.0%) was lower than that observed in a study performed in sub‐Saharan Africa 8 which reported 32.3% of poor quality. In that study, carbamazepine and sodium valproate were the poorest in terms of quality, probably due to high sensitivity to humidity and heat under tropical conditions, whereas our study found poor quality only for phenobarbital samples.…”
Section: Discussionsupporting
confidence: 84%
“…Endpoints, sampling methodology, and analytical testing were adapted from those used in another project performed in sub‐Saharan Africa and published in 2018 8 . A degree of quality scale was designed based on type of issue(s) observed (active ingredient assay, impurities screening, pharmacotechnical features) (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endpoints, sampling methodology, and analytical testing were adapted from those used in another project performed in sub‐Saharan Africa and published in 2018 11 . A degree of the quality scale was designed based on the type of issue(s) observed (active ingredient assay, impurities screening, pharmacotechnical features) (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in Lao PDR, approximatively half of the sample of phenobarbital collected in 2018, which was the most available and affordable ASM, was of poor quality 8 . Besides, a study performed in sub‐Saharan Africa shown that tropical environmental factors (temperature, relative humidity, light) have a strong influence on the quality of carbamazepine, phenytoin, and sodium valproate tablets 11 …”
Section: Introductionmentioning
confidence: 99%